Pemanfaatan Ternak dalam Pengendalian Nyamuk Vektor Penyakit - ARSHI Veterinary Letters FKH IPB; Susi Soviana; Upik Kesumawati Hadi; Fahmi Khairi; . Supriyono; Imam Hanafi (ARSHI Veterinary Letters, 2020)
Mosquito are insects that cause the most health problems in society and animal, namely as nuisance insects and vector of various diseases such as malaria, dengue hemorrhagic fever, chikungunya, Japanese Encephalitis, dirofilariasis, filariasis, St. Louis Encephalitis and West Nile Virus. Control of mosquito as a vector with utilization of cattle (zooprophylaxis) needs to be done so the role of cattle is more optimize. This study aimed to know the effect of the placement of cattle around population to reduce contact between mosquitoes and human. Catching mosquitoes was done at home with two treatments, the house with cattle and house without cattle. Catching mosquitoes in human by bare leg collection method at indoor and outdoor and cattle were placed in a magoon trap. The result showed density of Cx. sitiens are known as vector of Japanese Encephalitis in human at house with cattle 12.05 mosquitoes/man/hour, in human at house without cattle 16.31 mosquitoes/man/hour, and in cattle 54.38 mosquitoes/cattle/hour. Density of Anopheles are known as vector of malaria were caught showed placement of cattle reduce contact between mosquitoes and human. Density of An. sundaicus in human at house with cattle 0.03 mosquitoes/man/hour, in human at house without cattle 0.01 mosquitoes/man/hour, and in cattle 9.63 mosquitoes/cattle/hour. This research showed placement of cattle as zooprophylaxis media around population divert mosquitoes from human to animal